Representation of the Older Adults in the Media: Examples from an Old Age-Themed Short Film Competition - Merve Ayar Yılmaz; Büşra Turan Tüylüoğlu (Senectus)
This study delves into the portrayal of old age in Turkish media through an analysis of short films centered on aging. Specifically, it examines the potential for positive representations of the older adults in Turkey. Short films selected from the 2015 short film competition organized by the 65+ Elderly Rights Association serve as the primary subjects for content analysis regarding the depiction of old age. The films under scrutiny include “Altın Kızlar,” “Misafir,” “Lübbeyin Yaşlıları,” “Deneyim,” “Bir Anı,” and “Üreten Yaş Almaz.” Moreover, the research supplements its analysis with in-depth interviews conducted with the directors who participated in the aforementioned competition. These interviews provide valuable insights into how the older adults and aging are portrayed in Turkish cinema. Through this approach, the study aims to assess the potential for a more positive and socially realistic portrayal of the older adults within the national media landscape, contrasting prevalent negative stereotypes. Ultimately, the findings indicate that media representation of the older adults is heavily influenced by the preferences of content producers, largely dictated by market forces rather than genuine societal perceptions.